Issues for the Performance Monitoring of an Open Source H.323 Implementation Ported to IPv6 – Enabled Networks with QoS Characteristics - Christos Bouras; Apostolos Gkamas; Kostas Stamos; Dimitris Primpas; A Karaliotas (The 2003 International Conference in Internet Computing (IC 2003), Las Vegas, Nevada, USA, 2003)
OpenH323 is an open source H.323 implementation that has been ported to IPv6. It therefore presents an opportunity to perform experiments and compare the performance of an H.323 application when using the IPv4 stack and when using the IPv6 stack. In this paper we initially introduce briefly the porting procedure and the methodology we used in order to achieve it. We then present the appropriate experiments that have to be performed in order to comparatively evaluate the IPv4 and IPv6 protocol stacks. We also present the results of some initial experiments comparing IPv4 and IPv6 performance and the conclusions that they can lead us to.